1988
DOI: 10.1002/ar.1092220113
|View full text |Cite
|
Sign up to set email alerts
|

Extragonadal distribution of primordial germ cells in the early chick embryo

Abstract: Chick primordial germ cells (PGCs), after separation from the endoderm in early embryonic development, temporarily circulate via the blood vascular system and finally migrate into the gonadal anlagen. It has been noted by some authors that some PGCs are present in extragonadal sites in some vertebrates. In the present study, we examined the distribution and localization of PGCs in extragonadal sites in the chick embryo. PGCs were identified by periodic acid-Schiff staining with light microscopy. In embryos at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 14 publications
5
26
0
Order By: Relevance
“…In chickens, the optimal developmental stages for collection of PGCs were stages 14 and 15, in both the S.II-cultured embryos and the control intact embryos. Previous studies have shown that in intact chick embryos the highest number of PGCs circulate in the blood vessels during stages 13 and 15, and that the number of circulating PGCs varies with the developmental stage [Singh and Meyer, 1967;Nakamura et al, 1988;Tajima et al, 1999]. The present results using the S.II-cultured embryos showed, in accordance with those previous findings, that the number of PGCs circulating in the bloodstream (and recoverable) reached a peak at stage 14 and then decreased.…”
Section: Discussionsupporting
confidence: 95%
“…In chickens, the optimal developmental stages for collection of PGCs were stages 14 and 15, in both the S.II-cultured embryos and the control intact embryos. Previous studies have shown that in intact chick embryos the highest number of PGCs circulate in the blood vessels during stages 13 and 15, and that the number of circulating PGCs varies with the developmental stage [Singh and Meyer, 1967;Nakamura et al, 1988;Tajima et al, 1999]. The present results using the S.II-cultured embryos showed, in accordance with those previous findings, that the number of PGCs circulating in the bloodstream (and recoverable) reached a peak at stage 14 and then decreased.…”
Section: Discussionsupporting
confidence: 95%
“…The present results are in agreement with those of Yasuda et al [7], who transferred 100 chick PGCs into the marginal sinus of 2.5-day-old quail embryos and found that approximately 63 and 13% of the PGCs were in the gonadal and extragonadal regions of the quail embryos 24 h after transfer, respectively. Nakamura et al [25] reported that the proportion of extragonadal PGCs in the normal developing 3-day-old chick embryo at stage 19 [6] is 15.5%. These results indicate that extragonadal migration of chick PGCs occurs probabilistically in normal Chick PGC located in the mesenchyme of the trunk (arrow).…”
Section: Discussionmentioning
confidence: 99%
“…The chick PGCs migrate into the germinal ridge [1][2][3][4], where they differentiate into either spermatogonia in the testis or oogonia in the ovary. The unique migratory pathway of avian PGCs facilitates their isolation and transfer, especially from the blood vessels.…”
Section: Introductionmentioning
confidence: 99%